Pengaruh Kesiapan ASEAN Economic Community Terhadap Hubungan Organization Citizenship Behavior Dengan Kinerja Perusahaan - Mandhala, Yogia Dana; Pradhanawati, Ari; Ngatno, Ngatno (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2016)
In its activity, small scale industries facing with the competitive from different angles of factor which affect it, one of many factors is global regulation. In held of ASEAN Community in early 2016 will affect the way business activites and capable to change business environment. This research especially addresses how Micro, Small and Medium Enterprises (MSMEs) facing ASEAN Economic Community especially in Semarang County, affect the relation between individual performance and MSME’s performance.This study aims to determine the effect of relation between Organization Citizenship Behavior and MMEs Performance with Preparation Facing ASEAN Economic Community as a moderating variable, Type of explanatory research, data collection techniques are interviews with the tool questionnaire, sampling technique purposive sampling with a sample size 50 MSME’s. The data were analyzed through correlation coefficient, determination coefficient, simple linear regression, regression moderation, and t test. The data were analyzed quantitatively using software SPSS and qualitative.The result showed that Organizational Citizenship Behavior categorization is quite high. Then the MMEs Performance categorization is high enough. The Organizational Citizenship Vehavior has a quite high influence on the MSME’s Performance (49.2 percent) as well as the significant and positive impact on the MSME’s Performance (0.701). Preparation Facing ASEAN Economic Community is a potential moderating variable by variable regression coefficient of MSME’s Performance not significant. In Conclusion, the higher level of Organizational Citizenship Behavior, the higher MSME’s Performance and Preparation Facing ASEAN Economic Community have potential to become moderation variable. MMEs suggested to improve the awareness of worker on MSME’s development and improve outwork activity which can create good name for enterprises. Beside that, MSME’s unnecessary considering Preparation Facing ASEAN Economic Community in making policy decisions to improve MSME’s Performance but should focus more on improving the Organizational Citizenship Behavior.